Motivasi Belajar IPA di Tingkat Sekolah Dasar di Masa Pandemi - Sahilfah Sahilfah; Iva Sarifah; Imaningtyas Imaningtyas (Universitas Negeri Makassar, 2021)
This study aims to determine the motivation to learn science for elementary school students during the Covid-19 pandemic and to find out the supporting and inhibiting factors for learning science motivation for elementary school students during the Covid-19 pandemic at SDN 08 Petang. This type of research is qualitative with data collection in the form of distributing questionnaires through google forms with class III subjects at SDN 08 Evening. Data analysis technique using descriptive method. The results show that the motivation to learn science in class III at SDN 08 Petang is very varied. There are several factors that support and hinder the motivation to learn science during the Covid-19 pandemic. Factors supporting motivation in learning science are communication tools (mobile/laptop), internet network, internet quota, use of resources in learning, and praise given by the teacher. While the inhibiting factors for learning science motivation during the pandemic are parents who do not limit students to playing cellphones and also too many tasks given by teachers. There are many impacts of courageous learning. Therefore, teachers and parents play an important role in supporting and motivating student learning.